Experimental First Order Pairing Phase Transition in Atomic Nuclei. (9th February 2015) - Moretto, L G; Larsen, A C; Giacoppo, F; Guttormsen, M; Siem, S
Abstract: The natural log of experimental nuclear level densities at low energy is linear with energy. This can be interpreted in terms of a nearly 1st order phase transition from a superfluid to an ideal gas of quasi particles. The transition temperature coincides with the BCS critical temperature and yields gap parameters in good agreement with the values extracted from even- odd mass differences from rotational states. This converging evidence supports the relevance of the BCS theory to atomic nuclei.